X2 + 12 = 7x x2 – 7x + 12 = 0factor the equation (x – 3 ) ( x – 4 ) = 0 Then equating both factor to 0 X – 3 = 0 X = 3 And X – 4 = 0 X = 4 So the answer is X = 3 X =4
Answer:
When point A with coordinates (0, -1) is reflected across the x-axis and mapped onto point A', the coordinates of A' will be (0, 1).
i.e A'(0, 1) is the image of point A after a reflection.
Hence, point A is reflected across the x-axis.
Step-by-step explanation:
When we reflect a point A across the x-axis, the value of 'y' gets negated, but the value of 'x' remains unchanged.
In other words, when point P with coordinates (x, y) is reflected across the x-axis and mapped onto point P', the coordinates of P' will be (x, -y).
Thus, the rule is:
P(x, y) → P'(x, -y)
Thus, when point A with coordinates (0, -1) is reflected across the x-axis and mapped onto point A', the coordinates of A' will be (0, 1).
i.e A'(0, 1) is the image of point A after a reflection.
Hence, point A is reflected across the x-axis.
Caroline, Colin & Sarah share some money.Caroline will get when Caroline, Colin & Sarah share some money.
<h3>What is the ratio?</h3>
The ratio defined as the sharing of the two or three things or it represent that one thing or number is how many times to the other.
One part is excluded in the problem. That part is:
"Caroline gets of the money."
If Caroline gets 1/9th, then remaining is:
Colin and Sarah share in ratio 3 is to 1, that means 3 + 1 = 4 parts...
8/9th in 4 parts means, each part is:
We know Colin gets "3" parts of the total, each part is (2/9)th, so 3 parts would be:
Colin gets money when three of them share money.
To know more about Ratio follow
brainly.com/question/2328454
#SPJ1
(x - 3) + (x - 6) + x = 63
x - 3 + x - 6 + x = 63
Combine like terms
3x - 9 = 63
Isolate the constant
3x - 9 + 9 = 63 + 9
3x = 72
Isolate the viable
3x / 3 = 72 / 3
x = 24
Answer:
do da dash in the whip fo i fu6 a nica bih
Step-by-step explanation: